...sicut cera imprimitur sigilloMnemotechnics in the sermons of Peregrine of Opole - KIEŁBUS, MARCIN (Journal of Education Culture and Society, 2020)
This article demonstrates the functioning of ars memorativa in the works of Peregrine of Opole. Analyzing one of his sermons, we can see the presence of an ancient technique called imagines agentes.